Dedications of exams in elementary schools and colleges of the Mexico City and Veracruz, 1824-1868 - Martínez Carmona, Pablo (Historia y Memoria de la Educación, 2020)
The dedication of examinations to religious, patriotic, heroic and civil characters and images was part of the ceremonial educational world in nineteenth-century Mexico. These school practices were related to a transmission of feelings of devotion to hierarchies and paternalism. This article reviews the meaning of these dedications in fundamental aspects, such as schooling, citizenship and national identity. The article is structured in two sections that refer, on the one hand, to the use of these dedications in elementary education and, on the other hand, in the higher education given in colleges and institutes. The analysis is based on Mijail Bajtin´s discourse genres and the concept of construction of Maurice Agulhon's idealizations; the notions of paternalism, construction of the hero and the formation of political loyalties are also used. The time frame covers from the emergence of First Federal Republic in 1824 until the dawn of the Restored Republic in1868. The focus of the study is Mexico City, the capital of the country, which had the greatest concentration of educational establishments. For the purpose of regional comparison, the cases of two cities in the eastern state of Veracruz, Xalapa, the capital, and Veracruz, the republic's main port, are also reviewed.